ENT530: Company analysis of Ahmad Lim Black Pancake / Nur Ain Mohamed Abdul Fatah, Nuraqila Zulkifli and Musliza Munirah Che Musa - Mohamed Abdul Fatah, Nur Ain; Zulkifli, Nuraqila; Che Musa, Musliza Munirah (2017)
The product that has chosen by our group is Ahmad Lim Black Pancake. Ahmad Lim black pancake was founded by Uncle Ahmad Lim in 2015. Within the food and beverage industry in Malaysia, Ahmad Lim Black Pancake is like the pioneer in introducing the black pancake into . Malaysian market. The main mission of Ahmad Lim Black Pancake is to give maximum delicacy to their customers. Because of this their followers are willing to spend more for personal satisfaction. As we know, not all customers are willing to spend more on foods. We would like to proposed the best solutions in order to enhance Ahmad Lim existing business plan so that the products can be enjoy by everyone and to analyze the product and services that offered by Ahmad Lim company.